EthicHub: value-creating blockchain - Zhelezniak, Tanya (Henry Stewart Talks, 2023)
This case study showcases crowd-lending platform, EthicHub, as an example of blockchain usage creating value for participants in the ecosystem, achieving social impact as well as business purpose.